Clinical Outcomes of Ceftazidime–Avibactam versus Ceftolozane–Tazobactam in Managing Pseudomonal Infections in Patients Undergoing Renal Replacement Therapy - Wasim S. El Nekidy; Mooza Al Ali; Emna Abidi; Rania El Lababidi; Diaa Alrahmany; Islam M. Ghazi; Mohamad Mooty; Fadi Hijazi; Muriel Ghosn; Jihad Mallat (Antibiotics, 2024)
The optimal doses of ceftazidime–avibactam (CZA) and ceftolozane–tazobactam (C/T) for treating multidrug-resistant (MDR) Pseudomonas aeruginosa (PSA) in patients utilizing renal replacement therapy (RRT) are not well established. Hence, the objective of this study is to evaluate the clinical outcomes associated with the suggested doses of CZA and C/T in patients with PSA infection utilizing RRT. Methods: This is a retrospective study conducted at our hospital between September 2018 and March 2022. Clinical cure was the primary endpoint, while microbiologic cure, 30-day recurrence, and 30-day mortality were the secondary endpoints. Results: In total, 45 subjects met the inclusion criteria, with 25 receiving CZA and 20 receiving C/T. The median age was 69 (52–81) and 69 (61.5–83) years, respectively, while the median weight was 70 (55.5–81.5) and 66 (57–79) kg, respectively. Clinical cure was achieved in 12 (48%) subjects in the CZA group and 12 (60%) in the C/T group (p = 0.432). Of the 36 subjects who had repeated cultures, a microbiologic cure was achieved in 14/23 (60%) subjects and 10/13 (76.9%) subjects (p = 0.273). Thirty-day recurrence was reported in 3 (12%) cases in the CZA group and 6 (30%) in the C/T group (p = 0.082). The 30-day mortality was 13 (52%) subjects in the CZA group and 10 (50%) in the C/T group (p = 0.894). The median maintenance dose of CZA was 1.88 (0.94–3.75) g and 2.25 (1.5–2.25) g for C/T. Multivariate logistic regression analysis indicated that both drugs did not differ significantly in clinical cure. Bloodstream infection (BSI) (OR = 25, 95% CI: 1.63–411.7, p = 0.021) was the only independent factor associated with clinical cure in this population. Conclusions: Our findings indicated that C/T and CZA did not significantly differ in achieving clinical cure in patients with MDR PSA infections undergoing RRT. Larger clinical trials are needed to confirm our findings.